Powaqqatsi [videorecording (DVD)] - Coppola, Francis Ford, 1939-; Lucas, George, 1944-; Reggio, Godfrey (Criterion collection, 2012)
Here, Reggio turns his sights on third-world nations in the Southern hemisphere. Forgoing the sped-up aesthetic of the first film, Powaqqatsi employs a meditative slow motion in order to reveal the beauty of the traditional ways of life in those parts of the planet, and to show how cultures there are being eroded as their environments are taken over by industry.